Optimum Substrate for the Establishment of the Epiphyte Dischidia nummularia (Asclepiadaceae) - Abd Rahman, Khatijah; Kiew, Ruth (1986)
Brick fragments or wood crumbs (which are substrates with good water retention and aeration) with the addition of nutrients are optimum substrates for the establishment of seedlings of the epzphytic Dischidia ·nummularia. Seeds of D. nummularia, when moistened show 100% germination. Germination is rapid - the radicle is fully grown within a day and the cotyledons emerge within four to five days. Subsequent seedling growth, especially for root system development, was better on brick fragments or wood crumbs than on sand indicating that good water retention and aeration are necessary for seedling establishment. Within an eight-week period, seedling growth on substrates low in nutrients was slow compared with substrates where commercial fertilizer was applied in the recommended amount for epiphytic orchids. The height and number of leaves was roughly doubled and the total dry weight increased between three and fourfold. Further, with brick fragments as a substrate, addition of nutrients resulted in a more extensive root system.